2016
DOI: 10.1002/prp2.248
|View full text |Cite|
|
Sign up to set email alerts
|

Fibromyalgia syndrome: metabolic and autophagic processes in intermittent cold stress mice

Abstract: Fibromyalgia is characterized by widespread musculoskeletal pain, fatigue, and depression. The aim was to analyze potential mitochondrial dysfunction or autophagy in mice after exposure to intermittent cold stress (ICS). Muscle and liver specimens were obtained from 36 mice. Lactate dehydrogenase (LDH) activity was measured. Microtubule‐associated protein light chain 3 (MAP1LC3B) and glycogen content were determined histologically; muscle ultrastructure by electron microscopy. Mitochondrial‐ and autophagy‐rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
(115 reference statements)
2
6
0
Order By: Relevance
“…Our results using a hyperalgesic priming model are consistent with the muscle effects obtained in other experimental models of FM induced by depletion of biogenic amines 34,35 or intermittent cold stress. 7,36 In these studies, the authors observed not only muscle atrophy, but also an increase in the expression of atrogenes 34 and mitophagy, 36 as well as an imbalance in muscle antioxidant capacity. 34 These structural and metabolic disturbances could, at least partially, justify the changes in musculoskeletal functionality observed in FM patients.…”
Section: Discussionmentioning
confidence: 92%
“…Our results using a hyperalgesic priming model are consistent with the muscle effects obtained in other experimental models of FM induced by depletion of biogenic amines 34,35 or intermittent cold stress. 7,36 In these studies, the authors observed not only muscle atrophy, but also an increase in the expression of atrogenes 34 and mitophagy, 36 as well as an imbalance in muscle antioxidant capacity. 34 These structural and metabolic disturbances could, at least partially, justify the changes in musculoskeletal functionality observed in FM patients.…”
Section: Discussionmentioning
confidence: 92%
“…The increased demonstrating the expression of the autophagy markers and the appearance of ultrastructure changes in the mitochondria, indicating marked autophagy of the mitochondria. It was reported that in early autophagosomes, the mitochondria are degraded in response to oxidative stress [ 46 ], making it a significant source of ROS, especially in conditions that are associated with mitochondrial damage and stress [ 49 ] such as in fibromyalgia [ 50 ]. The mitochondrial dysfunction in fibromyalgia agrees with the data published by Martínez-Lara et al, [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…White mitochondria were assessed as damaged mitochondria, according to a previous study. [ 53 ]…”
Section: Methodsmentioning
confidence: 99%
“…White mitochondria were assessed as damaged mitochondria, according to a previous study. [53] Plasma Hemolysis Assay: Hemoglobin concentration was measured to determine hemolysis after high-intensity running and was measured by measuring the plasma absorbance at 380, 415, and 450 nm. [54] The iron content in the plasma was measured by inductively coupled plasma-mass spectrometry (ELAN DRC-e, Perkin Elmer, USA).…”
Section: Observation Of the Mitochondria Using Transmission Electron Microscopymentioning
confidence: 99%